(untitled) (El-Wahat Journal for Research and Studies, 2020)
Despite the growing importance of legal information in the economic field; accessibility to this type of information remains a real headache for economic actors. A reality that poses on public authorities the burden of making available sufficient and credible legal information, which can be achieved by adopting the principle of legal certainty. Economic actors are also called upon to be more efficient in collecting, processing and analyzing data in the context of developing the legal information they need, which can be achieved through legal intelligence techniques. Key words- *Legal certainty *Legal intelligence *Legal information *Economic intelligence *Investment.